APPLICATION OF SUPERSONIC RADIATION WAVE MODELS TO FLAMES SPECIFICATION IN RECIPROCATOR - Evgeny N. Ladosha; Denis S. Tsymbalov; Oleg V. Yatsenko (Вестник Донского государственного технического университета, 2018)
Some relations between various auto- and soliton models are investigated. Common features in the problem formulation of combustion, supersonic radiation wave propagation and moving of soliton wave on soundings are revealed. Realization of the known mathematical solutions for wave flame structure characterization in the reciprocating motor grain is proved.